Development and Quality of Rica-Rica as Indonesian Traditional Food: A Narrative Review - Nur Agustin Mardiana; Nur Aini Mahmudah; David Kurniawan; Anang Widigdyo; Aditya Wirawantoro Putra; Panji Purnomo (G-Tech: Jurnal Teknologi Terapan, 2026)
This narrative review explores rica-rica, a traditional North Sulawesi spicy dish, examining its historical roots, production process, and contemporary adaptations. Literature searches were conducted from January to August 2025 across major databases (PubMed/MEDLINE, Scopus, Web of Science, Google Scholar) and Indonesian repositories (Garuda Portal, Indonesian Publication Index), yielding 48 relevant sources. Rica-rica, characterized by intense chili heat, holds philosophical significance for Minahasan people who liken spiciness to life's inevitable challenges. The preparation involves grinding and sautéing spices, then cooking with various meats including poultry, mammals, seafood, and game animals. Meat selection significantly affects nutritional content, with protein ranging from 12.1% (broiler chicken) to 82.96% (dried snails). Game meat consumption, culturally valued by Minahasans, poses health risks from potential microbial contamination, viruses, and zoonotic diseases. Modern innovations such as instant seasonings, frozen products, and canned rica-rica, address contemporary demands while preserving culinary heritage. Although rica-rica offers culinary, cultural, and nutritional value, hygienic processing and safe ingredient selection are crucial to minimize consumer health risks. Future research should focus on empirical nutritional analysis, microbiological risk assessment along supply chains, and consumer acceptance studies of sustainable meat alternatives.